Biochemical and morphological responses to cadmium-induced oxidative stress in Cladophora glomerata - Celekli, Abuzer; Bulut, Hilal (Tubitak Scientific & Technological Research Council Turkey, 2020)
This study aimed to assess the effect of cadmium (Cd2+) concentrations on biovolume, pigments, malondialdehyde (MDA), hydrogen peroxide, proline, total phenolic compounds, total protein, and total carbohydrate contents of Cladophora glomerata. Cultivations of the alga (8.0 +/- 0.1 gas fresh weight) were exposed to 7.5, 15, 30, and 60 mg/L of Cd2+ ions in 500 mL flasks containing 400 ml of the medium on a shaker at 120 rpm for 7 days. Results of Fourier transform infrared analyses indicated that the amide, anionic, and amino groups had significant rolesin the binding of Cd2+ on C. glomerata. The detrimental effects of the Cd2+ dose not only observed the morphology of the algal cell but also changed the biochemical compounds of C. glomerata. Growth gradually decreased when the alga was exposed to Cd2+ at 15 and 60 mg/L in comparison with the control. High Cd2+ ions concentrations decreased in chlorophyll-a (from 14.27 mg/g in control to 9.97 mg/g at 60 mg/L Cd) and protein content (from 43.60 mg/g in control to 21.66 mg/g at 60 mg/L Cd) in the treated cells compared to the control group, whereas they increased stress molecules (e.g., MDA and proline) as biomarkers in the response mechanisms of algae to Cd2+ exposure. Results indicated that this alga had wide tolerance to high cadmium concentrations, and the stress compounds in the alga with exposure of Cd2+ seemed to be parameters as a biomarker for metal-induced oxidative stress.
Keywords: Biochemical response; cadmium; Cladophora glomerata; pigmentation